LIGHT INTENSITY LEVEL CONTROL - DARUSIS, ERWAN (Universiti Teknologi Petronas, 2006)
The purpose of the project is to design a light level intensity control using Light Dependent Resistor (LDR) sensor. The main task for the project is to develop a light detector circuit for controlling the light intensity level ina confined environment. The light intensity is measured by using the LDR sensor while the microcontroller is added to the circuit in order to detect and response to the light intensity and control the intensity level toa preset value. The effect ofdifferent amount of light allows the controller to switch at the desired intensity levels automatically. The dimmer uses the technique ofAC phase angle control, where the loads are turned on for a portion of the total AC line sinewave period. The changes of variable resistor value, will affect the starting firing angle. The methodology of this project includes literature survey, planning work, design, experimental/simulation step, implementation and documentation of development progress. Literature survey was done to find the existing AC phase control circuit that used to control the brightness/dimmer of the lamp (load). The design step includes developing a microcontroller programming for the automatically operation for brightness/dimmer purpose, PCB circuit design and prototype construction. The combination between microcontroller program and the AC phase angel control circuit allows the brightness/dimming a lamp to be controlled automatically depending on the lighting condition in a confined space. Therefore, the electrical power consumption could be controlled and thus it will be cost effective. Overall, this project has achieved its objective and functions according to specification. The brightness of the lamp (25 Watt) varies from a minimum load consumption (7.7 Watt) to a maximum load consumption (22.9 Watt) and therefore can be controlled to suit the lighting conditions.